Innovation Efforts in the Face of Institutional Obstacles in Latin America - Costa, Priscila Rezende da; Bittencourt, Vitor da Silva; Falaster, Christian Daniel; Carvalho, Luisa Margarida Cagica; Pigola, Angelica (International Journal of Business, Economics and Management, 2020)
Among scholars, politicians and practitioners, innovation has become a priority. However, a consensus and convergence have yet to be reached in the literature regarding the factors that determine innovation efforts at the firm level regarding developing countries. Thus, the general aim was to gauge to what extent rapid internationalization and relational triggers enable a potential for innovation efforts in companies from Latin American countries faced with the perception of the gravity of institutional obstacles. In methodological terms, a database of the World Bank (Environment Surveys) was used, with 14,064 companies from 20 Latin American countries, with responses to question related to their innovation efforts. Unprecedented contributions were collected, as this was the first time that the perception of the gravity of institutional obstacles was jointly and empirically evaluated, together with evidence of rapid internationalization and the use of relational triggers, to explain innovation efforts, considering many firms from Latin American companies. This work also provides some clues about the potentializing effect of rapid internationalization in the relationship between institutional obstacles and innovation efforts. The main results allow a better understanding about inter- and intra-group analyses, demonstrating in which groups of Latin American company’s innovation efforts are more significant and distinctive, and therefore require pro-market and pro-internationalization public policies.